A Poem Analysis of E.E. Cummings’ [I carry your heart with me (I carry it in] Grammatical and Phonological Level - Pramudana Ihsan (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2018)
Pramudana IhsanUniversitas Muhammadiyah Surabayapramudanaihsan@fkip.um-surabaya.ac.id AbstractEdward Estlin Cummings (1894-1962) was not a person who was trifling in the literary world. His ideas of several new writing styles were publicly known and were able to inspire many poets in this world. The new ideas of writing styles including lowercase writing on a few subjects, lack of commas, full stops, spaces, and also parentheses which are placed on the wrong spots. All of those things are manifested on the one of his great poems, titled [i carry your heart with me (I carry it in]. Even though several persons called the ideas as “peculiar ideas,” but the poet, made those peculiar ideas and also the deep sentences inside as the media to analyze this poem until it was able to be understood and discussed as literary subject. The phonological level analysis used sound devices understanding and semantics analysis which recommended by Fromkin, Rodman, & Hyams (2011: 148), used figure of speech recognizing; are maximally optimized in this work in order to serve the appropriate result as it is hoped, to be one of learning media in the literary discussion.   Keywords: Edward Estlin Cummings, phonological level analysis, grammatical level  AbstractEdward Estlin Cummings (1894-1962) merupakan orang yang terkenal dalam dunia sastra. Ide-idenya tentang gaya penulisan baru telah dikenal publik dan mampu menginspirasi banyak penyair di dunia, termasuk penulisan huruf kecil pada beberapa subjek, kurangnya koma, berhenti penuh, spasi, dan juga tanda kurung yang ditempatkan di tempat yang salah. Semua hal itu atertuang dalam puisinya yang berjudul (I carry your heart with me). Meskipun beberapa orang menyebut ide sebagai "ide yang aneh," tetapi dia mampu menuangkan ide tersebut dalam bait- bait puisi yang mendalam dari segi analisis tingkat fonologis berdasarkan suara dan analisis semantik yang direkomendasikan oleh Fromkin, Rodman, & Hyams (2011: 148). Selain itu, pengenalan kata- kata kiasan digunakan secara optimal sebagai salah satu media pembelajaran dalam diskusi sastra.Kata kunci: Edward Estlin Cummings, analisis tingkat fonologi, level gramatikal